Manajemen Layanan Konseling Adaptif Deep Learning, dengan Pendekatan Cognitive Behavioral Therapy - Khasanah, Fitri Uswatun; Jumintono, Jumintono; Mulyono, Rahmat (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2025)
The imbalance between cognitive and affective aspects in the formal education system in Indonesia indicates the need for a more adaptive and integrative counselling service approach. This research aims to develop an educational counselling service management model that integrates the cognitive behavioural therapy approach with the deep learning approach as a solution to the problem. Using a literature review method of recent literature (2023-2024), this article identifies the main contributions of deep learning in learning, particularly in terms of learning personalisation, emotional detection, and data-driven psychological intervention. The findings show that the integration of deep learning and cognitive behavioural therapy enables the development of a counselling model that is able to detect learners' psychological needs in real-time and provide appropriate interventions automatically. The results are expected to strengthen the psychosocial support system in the educational environment, improve learners' well-being, and encourage the creation of a holistic and sustainable learning environment. This research provides a conceptual contribution to the development of deep learning adaptive education policies that are more responsive to the needs of students as a whole.